Banking structures and sources of finance in the Far East - Banker Research Unit (London : Financial Times Business Publishing Ltd, 1980)
The present study consists essentially of a full revision of the 1977 edition. It relates to banking operations in the Far East i.e. Australia, New Zealand, The Philippines, Malaysia etc.
osa; 10/07/18
Loans
Keywords: Banks and banking; Southeast Asia